ALG-9 Congenital Disorder of Glycosylation: A Patient with Novel Variants and No Dysmorphism - Goswami, Jyotindra Narayan; Roy, Shuvendu (Journal of Pediatric Neurology, 2020)
We report a child with ALG-9 congenital disorder of glycosylation (ALG9-CDG) with two novel missense variants on clinical exome sequencing. Unlike the 11 previously reported patients, index child did not have dysmorphism. The case portrays the clinical heterogeneity of ALG-9 CDG.
Keywords: congenital disorder of glycosylation; ALG-9; epilepsy